Issue Information. Issue 4 (16th August 2021) - Unknown
Abstract : Spring barley (Hordeumvulgare L. cv. Barke) was grown in rhizoboxes in the greenhouse facility of Leuphana University of Lüneburg, Germany. Cover picture is showing spring barley roots sliced at 10 cm depth interval in rhizobox. Van Duijnen et al. investigated the root system responses non‐destructively over time and plant biomass allocation at the end of spring barley under differential timing of fertilizer application. Photo credit: Richard van Duijnen, Leuphana University of Lüneburg, Germany